Verba Berprefiks Ber- pada Buku Cerita Anak: Kajian Proses Afiksasi - Shakti, Zasqia Damai Aulia; Kesuma, Tri Mastoyo Jati (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
Children's storybooks play a crucial role in children's language development, thus demanding meticulous attention from authors in word selection and usage within the narrative. A comprehensive understanding of the morphological processes, particularly affixation, is essential for grasping the writing style. This study focuses on scrutinizing the morphological processes, particularly affixation, specifically the prefix ‘ber-’, on verbs. The analysis centers on the fundamental form and semantic formation. The dataset comprises all verbs prefixed with ber- sourced from a children's storybook titled "Cerita Negeri Tetangga: Kumpulan Dongeng Asia Tenggara" by Hapsari Hanggarini. The research adopts a qualitative descriptive approach to present the data. The findings reveal four fundamental forms of verbs with the prefix ‘ber-’and seven semantic formations. The prevalent fundamental form constitutes free morphemes, with the dominant semantic formation reflecting active actions. These findings suggest that affixation processes in children's storybooks tend to remain straightforward, catering to concepts accessible to children.